Pengembangan aspek moral dalam Pendidikan Kewarganegaraan SD dan SMP: Respons atas realitas keprihatinan moral - Suharno, Suharno (Jurnal Civics: Media Kajian Kewarganegaraan, 2016)
The reality of Indonesian people's life experienced the phenomena of depleted horizon moralities politically, legally, socially, and culturally. Civic education and learning process in the classroom could be a locomotive for moral improvement for Indonesian people. The crucial point in acting or doing something is not gun but man behind the gun. So teacher is the most important actor in this endeavor.